3D-Printed PCL scaffolds combined with juglone for skin tissue engineering - ŞAHİN, ALİ (My University, 2022)
Skin diseases are commonly treated with antihistamines, antibiotics, laser therapy, topical medications, local vitamins, or steroids. Since conventional treatments for wound healing (skin allografts, amnion, xenografts, etc.) have disadvantages such as antigenicity of the donor tissue, risk of infection, or lack of basement membrane, skin tissue engineering has become a popular new approach. The current study presents the design and fabrication of a new wound-dressing material by the addition of Juglone (5-hydroxy-1,4-naphthoquinone) to a 25% Polycaprolactone (PCL) scaffold. Juglone (J) is a significant allelochemical found in walnut trees and, in this study is used as a bioactive material. The effects of different amounts of J (1.25, 2.5, 5, 7.5, and 10 mg) on the biocompatibility, mechanical, chemical, thermal, morphological, and antimicrobial properties of the 3D-printed 25% PCL scaffolds were investigated. The addition of J increased the pore diameter of the 25% PCL scaffold. The maximum pore size (290.72 ± 14 µm) was observed for the highest amount of J (10 mg). The biocompatibility tests on the scaffolds demonstrated biocompatible behavior from the first day of incubation, the 25% PCL/7.5 J scaffold having the highest viability value (118%) among all of the J-loaded scaffolds. Drug release of J into phosphate buffered saline (PBS) at pH 7.4 showed that J was completely released from all 25% PCL/J scaffolds within 7 days of incubation
Keywords: Juglone; PCL; skin tissue engineering; scaffold; wound dressing; 3D printing; enhanced healing